Die ontwikkeling van 'n groeiende bevrydingsbediening: 'n literatuuroorsig veral met verwysing na invloedryke persone en kerklike tradisies - J. P. J. Theron (Acta Theologica)
Recent developments in the church’s ministry of deliverance have been investigated in terms of influential people and available literature. The period from the fifties to the eighties of the previous century is covered in the present literary investigation. It has been found that this new emphasis on the ministry of deliverance originated more or less at the same time in different parts of the world. Different individuals, not related to each other became involved because of their experiences and/or studies. The material shows that this ministry is practised in most denominations as well as by some medical and other professional care-givers. The need to develop a coherent practical theological theory is expressed.